Polycystic ovary syndrome as a plausible evolutionary outcome of metabolic adaptation - Daniel A. Dumesic; Vasantha Padmanabhan; Gregorio D. Chazenbalk; David H. Abbott (BMC, 2022)
Abstract As a common endocrinopathy of reproductive-aged women, polycystic ovary syndrome (PCOS) is characterized by hyperandrogenism, oligo-anovulation and polycystic ovarian morphology. It is linked with insulin resistance through preferential abdominal fat accumulation that is worsened by obesity. Over the past two millennia, menstrual irregularity, male-type habitus and sub-infertility have been described in women and confirm that these clinical features of PCOS were common in antiquity. Recent findings in normal-weight hyperandrogenic PCOS women show that exaggerated lipid accumulation by subcutaneous (SC) abdominal stem cells during development to adipocytes in vitro occurs in combination with reduced insulin sensitivity and preferential accumulation of highly-lipolytic intra-abdominal fat in vivo. This PCOS phenotype may be an evolutionary metabolic adaptation to balance energy storage with glucose availability and fatty acid oxidation for optimal energy use during reproduction. This review integrates fundamental endocrine-metabolic changes in healthy, normal-weight PCOS women with similar PCOS-like traits present in animal models in which tissue differentiation is completed during fetal life as in humans to support the evolutionary concept that PCOS has common ancestral and developmental origins.